2017
DOI: 10.1186/s13601-017-0153-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-morbidities of allergic rhinitis in adults: European Academy of Allergy and Clinical Immunology Task Force Report

Abstract: This report has been prepared by the European Academy of Allergy and Clinical Immunology Task Force on Allergic Rhinitis (AR) comorbidities. The aim of this multidisciplinary European consensus document is to highlight the role of multimorbidities in the definition, classification, mechanisms, recommendations for diagnosis and treatment of AR, and to define the needs in this neglected area by a literature review. AR is a systemic allergic disease and is generally associated with numerous multi-morbid disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
124
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 96 publications
(151 reference statements)
3
124
0
8
Order By: Relevance
“…Statistically, more than 50% of people with moderate to severe asthma also have chronic sinusitis indicating a direct connection between sinusitis and asthma; many studies show the connection between sinus infections and asthma [3]. One 2006 study showed that when compared with those who only have asthma, people who have both sinusitis and asthma tend to have more severe asthma symptoms, may have more severe asthma flare ups, and are more likely to have disturbed sleep [2].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Statistically, more than 50% of people with moderate to severe asthma also have chronic sinusitis indicating a direct connection between sinusitis and asthma; many studies show the connection between sinus infections and asthma [3]. One 2006 study showed that when compared with those who only have asthma, people who have both sinusitis and asthma tend to have more severe asthma symptoms, may have more severe asthma flare ups, and are more likely to have disturbed sleep [2].…”
mentioning
confidence: 99%
“…The aim is to educate and implement evidence based management of allergic rhinitis in conjunction with asthma worldwide. In the ARIA guidelines revision, 2008, the published supplement in the European Journal of Allergy and Clinical Immunology reviewing the latest scientific evidence on the definition of classification of rhinitis, risk factors mechanisms, and diagnosis and treatment with extensive citations in the scientific literature states in 6.9.2 "nasal obstruction is difficult to quantify directly by examination alone", so objective assessments such as acoustic rhinometry are used as an objective assessment [3]. This specific guideline remains since the 2010 review and revision giving additional perspective on the use of various treatments for allergic rhinitis.…”
mentioning
confidence: 99%
See 3 more Smart Citations